Transmission of viable Haemophilus ducreyi by Musca domestica - Stabile, Haley D.; McCandless, Kayla; Donlan, Rachel A.; Gaston, Jordan R.; Humphreys, Tricia L. (PLOS Neglected Tropical Diseases, 2024)
Author summary Cutaneous ulcers are prevalent throughout the world, especially in low/middle-income countries. The commonality of diseases that cause cutaneous ulcers makes the transmission mechanisms of these diseases of great interest to public health. Understanding the mechanism by which these diseases are contracted and transmitted greatly informs prevention and treatment strategies. This study investigates the potential for mechanical transmission of a bacterial pathogen, Haemophilus ducreyi, using the common house fly, Musca domestica. Mechanical transmission via insects is the process by which a pathogen adheres to the appendages or mouthparts of a vector, thereby allowing the vector to spread the pathogen from infected to uninfected individuals. During this study, live H. ducreyi was found to transfer from the surface of M. domestica onto agar plates via the flies’ innate behavior alone, suggesting flies are capable of transmitting the bacteria. This novel finding for H. ducreyi should be carefully considered in future prevention and treatment strategies for cutaneous ulcers caused by this pathogen and serves as a model for similar diseases.